Dança e transcendência: fragmentos de espiritualidade na contemporaneidade. - Moura, Décio Overarth Macedo de (2015)
Search the theme "Dance and transcendence: spirituality fragments in contemporary times", with the motivation to find answers even if provisional and unfinished, on human attempt at existential search for meaning. From the reports of the experiences of nine artists Dance Gifts in Pernambuco scenario, it was possible to establish relationships of their trajectories in contemporary danced with the transcendence and spiritual dimensions. The delivery of each interviewee revealed inspiring artist biographies built through dance, allowing underpin this work. The choices of the artists were equivalent to their contributions and the permanence of its activities in varied styles and social segments. Data were collected in semi-structured interview. In interviews, the artists reveal a spirituality and relationship with God, out of religious institutional context, which reflects the dynamics of transformation of religious phenomenon nowadays. The intertwined dynamics between dance, transcendence and spirituality, remains producing access roads so that the human being can find his way full. This work reveals synthesized form, the complex relationship between dance, transcendence and spirituality, requiring develop new studies that could deepen the knowledge about this issue.